1998
DOI: 10.1002/(sici)1097-0290(19980720)59:2<189::aid-bit7>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and simulation of complex interactions during dynamic microfiltration ofEscherichia coli suspensions

Abstract: Microfiltration is an important unit operation in downstream processing. However, due to the influence of membrane fouling, prediction of the filtration performance for biological suspensions is difficult. This paper describes a modeling approach that allows a comprehensive description of filtration performance. On the basis of experimental data and linguistic information, a specific artificial neural network was developed that predicts the process behavior within a certain range of parameters. This approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It was found that rod-shaped bacteria formed a cake with 100 times higher resistance than that formed by elliptical bacteria and showed a relationship between the compressibility and the void fraction of the cake. Within a single species of unicellular organisms the main effect has been shown to be the dry cell weight (Meyer et al, 1998). In the case of S. erythraea, as used here in the SCM broth, permeate flux was found to be independent of the fermentation time (Fig.…”
Section: Relationship Between Permeate Flux Broth Viscosity and Hypmentioning
confidence: 99%
“…It was found that rod-shaped bacteria formed a cake with 100 times higher resistance than that formed by elliptical bacteria and showed a relationship between the compressibility and the void fraction of the cake. Within a single species of unicellular organisms the main effect has been shown to be the dry cell weight (Meyer et al, 1998). In the case of S. erythraea, as used here in the SCM broth, permeate flux was found to be independent of the fermentation time (Fig.…”
Section: Relationship Between Permeate Flux Broth Viscosity and Hypmentioning
confidence: 99%
“…They solved the problem of flux decline by the design of inlet/outlet, disk structure, and the distance between rotating disk and membrane, mixing rate and TMP. Dynamic Membrane Filter (DMF, Pall Corp., Cortland, NY) appeared as the first commercial system [125,147,182]. This filtration unit houses a 6-in.-diameter stainlesssteel solid disk with a maximum rotating speed of 3450 rpm rotating in the clockwise direction only.…”
Section: Rotating Diskmentioning
confidence: 99%
“…This will, of course, be membrane‐specific. Meyer and colleagues (60) observed a flux reduction of 15% when cells were stored for 5 h at 4 °C and 30% reduction with freezing and thawing.…”
Section: Cell Harvestingmentioning
confidence: 99%